APLIKASI PENAMBAHAN PEMBENAH TANAH DARI Eichhornia crassipes Solms. DAN Salvinia molesta Mitchell. PADA TANAH PASIR DAN TANAH LIAT TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN TANAMAN ROSELLA (Hibiscus sabdariffa L.) - Amalia, Nur Rizki; Haryanti, Sri; Parman, Sarjana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Soil conditioner is materials that add to the soil. Soil conditioner can be improve soil structure, changing the capacity of the soil, hold and pull through the water, so it can support plant growth. This study aims to determine the effects of soil conditioner the germination and growth of rosella (Hibiscus sabdariffa L.) on sandy and clay soil. This research was conducted at Laboratory of Biological Structure and Function of Plant Biology, Faculty of Sains and Mathematic, Diponegoro University. This research was designed by completely random design with factorial pattern 2 x 3. This treatment was replicated 3 time. Ratio of soil and soil conditioner is 75%:25%. The result data analized by Analysis of Variance (ANOVA) continued by test Duncanâ€™s Multiple Range Test (DMRT) on 95% significance level. The parameters in this research were field capacity, viability, shoot length, number of leaf, fresh and dry weight. The results showed that addition soil conditioner from Salvinia molesta increase the germination of 20% and the addition soil conditioner from Eichhornia crassipes increase the germination of 30%. The addition soil conditioner from Salvinia molesta increase the plant growth of 17,45% and the addition soil conditioner from Eichhornia crassipes increase the plant growth of 20,94%. Application of theÂ addition soil conditioner from Eichhornia crassipes Solms. on clay soil more effective to increase field capacity, germination and plant growth of Hibiscus sabdariffa.